Microsatellites from Fosterella christophii (Bromeliaceae) by de novo transcriptome sequencing on the Pacific Biosciences RS platform1. (7th January 2016) - Wöhrmann, Tina; Huettel, Bruno; Wagner, Natascha; Weising, Kurt
Abstract : Premise of the study: Microsatellite markers were developed in Fosterella christophii (Bromeliaceae) to investigate the genetic diversity and population structure within the F. micrantha group, comprising F. christophii, F. micrantha, and F. villosula . Methods and Results: Full‐length cDNAs were isolated from F. christophii and sequenced on a Pacific Biosciences RS platform. A total of 1590 high‐quality consensus isoforms were assembled into 971 unigenes containing 421 perfect microsatellites. Thirty primer sets were designed, of which 13 revealed a high level of polymorphism in three populations of F. christophii, with four to nine alleles per locus. Each of these 13 loci cross‐amplified in the closely related species F. micrantha and F. villosula, with one to six and one to 11 alleles per locus, respectively. Conclusions: The new markers are promising tools to study the population genetics of F. christophii and to discover species boundaries within the F. micrantha group.